The last tourist - Steinhauer, Olen (Milo Weaver, 2020)
"New York Times bestselling author Olen Steinhauer brings back Milo Weaver in a new novel. In Olen Steinhauer's bestseller An American Spy, reluctant CIA agent Milo Weaver thought he had finally put "Tourists"-CIA-trained assassins-to bed. A decade later, Milo is hiding out in Western Sahara when a young CIA analyst arrives to question him about a series of suspicious deaths and terrorist chatter linked to him. Their conversation is soon interrupted by a new breed of Tourists intent on killing them both, forcing them to run. As he tells his story, Milo is joined by colleagues and enemies from his long history in the world of intelligence, and the young analyst wonders what to believe. He wonders, too, if he'll survive this interview. After three standalone novels, Olen Steinhauer returns to the series that made him a bestseller"--